2022
DOI: 10.1007/s00520-022-06915-9
|View full text |Cite
|
Sign up to set email alerts
|

Burden of hospitalizations and outpatient visits associated with moderate and severe acute graft-versus-host disease in Finland and Sweden: a real-world data study

Abstract: Purpose The aim of this study was to describe patient characteristics and quantify hospital stays and outpatient visits (H&OV) following diagnosis with moderate-to-severe acute graft-versus-host disease (aGVHD) in Finland and Sweden. Methods A retrospective chart audit collected data from patient medical records of 3 specialized centers performing allogeneic hematopoietic stem cell transplantation (HSCT; Finland, n = 2; Sweden, n = 1). Eligible patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Our group has previously shown that moderate to severe aGVHD is associated with high rates of hospitalizations and outpatient visits among patients receiving allogeneic HSCT at transplant centers in Finland and Sweden [ 18 ]. Taken together, findings from this study and previous reports demonstrate the substantial burden of aGVHD among allogeneic HSCT recipients and highlight the need for more effective treatment strategies that can improve clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our group has previously shown that moderate to severe aGVHD is associated with high rates of hospitalizations and outpatient visits among patients receiving allogeneic HSCT at transplant centers in Finland and Sweden [ 18 ]. Taken together, findings from this study and previous reports demonstrate the substantial burden of aGVHD among allogeneic HSCT recipients and highlight the need for more effective treatment strategies that can improve clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in staging and grading systems among sites (i.e., MAGIC vs. modified Glucksberg) may have affected the results, although an alignment process was performed to ensure compatibility across grading systems (Supplementary Figures S1–S3 ). The alignment process grouped and mapped modified Glucksberg cases into MAGIC (instead of doing the opposite, i.e., mapping or naively comparing patients graded in MAGIC with patients graded in Glucksberg) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations